Two Keggin polyoxometalate-based hybrid compounds with different helix: Syntheses, structure and catalytic activities. (27th July 2017) - Zhu, Peipei; Sheng, Ning; Liu, Guodong; Sha, Jingquan; Yang, Xiya
Graphical abstract: Two new Keggin POMs-based hybrids with different helix were synthesized under different pH value, which exhibits good catalytic activities of esterification. Abstract: By adjusting pH value, two new Keggin polyoxometalate-based hybrid compounds with different helical structure, [Ag6 (btp)(pyttz)6 ·(HSiMo12 O40 )2 ]·4H2 O (1 ) and [Ag2 (pyttz)4 ·(H2 SiMo12 O40 )2 ]·(TMA)2 ·4H2 O (2 ), (pyttz = 3-(pyrid-4-yl)-5-(1 H-1, 2, 4–3-yl)-1, 2, 4-triazolyl, btp = 5, 5′-di(pyridin-4-yl)-1 H, 1′H-3, 3′-bi(1, 2, 4-triazole), TMA = tetramethylammonium), were successfully isolated by hydrothermal reaction and structurally characterized. Structural analysis shows the nature of the inorganic meso-helical channel in compound1 and 2D homological helical layer in compound2. It is also interesting that a new organic ligand btp is formed in situ by the coupling of N-Heterocycle in1 . In addition, the catalytic activities of1 and2 as solid-acid catalyst are explored, and the results indicate that1 and2 are a kind of highly-efficient and promising solid catalysts. Additionally, the proposed generation mechanism of btp in situ is also discussed.